2010
DOI: 10.2169/internalmedicine.49.2837
|View full text |Cite
|
Sign up to set email alerts
|

Slowly Progressive Insulin-dependent Diabetes Mellitus Associated with Pernicious Anemia

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…We herein describe a patient with pernicious anemia that occurred 8 years after his diagnosis of acute-onset T1D. In addition, all 14 previously reported cases of Japanese patients with concomitant T1D and pernicious anemia are reviewed (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…We herein describe a patient with pernicious anemia that occurred 8 years after his diagnosis of acute-onset T1D. In addition, all 14 previously reported cases of Japanese patients with concomitant T1D and pernicious anemia are reviewed (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Hibi et al studied 1572 Japanese type 1 diabetes mellitus, thirty-three patients had autoimmune thyroid disease (2.10%) and only one patient had pernicious anemia [7]. Kinoshita et al reported that type 1 diabetes mellitus with coexisting pernicious anemia was approximately 8 cases in Japan [8]. …”
Section: Discussionmentioning
confidence: 99%